Chromosome-level assembly, annotation and phylome of Pelobates cultripes, the western spadefoot toad. (18th May 2022) - Liedtke, Hans Christoph; Cruz, Fernando; Gómez-Garrido, Jèssica; Fuentes Palacios, Diego; Marcet-Houben, Marina; Gut, Marta; Alioto, Tyler; Gabaldón, Toni; Gomez-Mestre, Ivan
Abstract: Genomic resources for amphibians are still hugely under-represented in vertebrate genomic research, despite being a group of major interest for ecology, evolution and conservation. Amphibians constitute a highly threatened group of vertebrates, present a vast diversity in reproductive modes, are extremely diverse in morphology, occupy most ecoregions of the world, and present the widest range in genome sizes of any major group of vertebrates. We combined Illumina, Nanopore and Hi-C sequencing technologies to assemble a chromosome-level genome sequence for an anuran with a moderate genome size (assembly span 3.09 Gb); Pelobates cultripes, the western spadefoot toad. The genome has an N50 length of 330 Mb with 98.6% of the total sequence length assembled into 14 super scaffolds, and 87.7% complete BUSCO genes. We use published transcriptomic data to provide annotations, identifying 32, 684 protein-coding genes. We also reconstruct the P. cultripes phylome and identify 2, 527 gene expansions. We contribute the first draft of the genome of the western spadefoot toad, P. cultripes . This species represents a relatively basal lineage in the anuran tree with an interesting ecology and a high degree of developmental plasticity, and thus is an important resource for amphibian genomic research.